1969
DOI: 10.3758/bf03336421
|View full text |Cite
|
Sign up to set email alerts
|

Conditional probability of reinforcement and sequential behavior in human conditioning with intermittent reinforcement schedules

Abstract: Fourteen Ss were exposed to three 50%-reinforcement sclledllills in human eyelid conditioning. The In the typical 50% reinforcement schedule the conditional probability of a reinforced trial following a reinforced trial, P(R IR), as weil as the conditional probability of a nonreinforced trial following a nonreinforced trial, P(R I ~), is . 5. When both P(R I R) and P(R I R) are increased (maintaining the 50% reinforcement ratio) increments and decrements in response prob ability following, respectively, rein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…The finding that conditioned responding was influenced not by expectancy but by the recent frequency of CS-alone and CS-US trials provides particularly strong evidence that delay eyeblink conditioning in humans is an example of nondeclarative memory and is unrelated to awareness (Clark & Squire, 1998;Grant, 1973;Papka, Ivry, & Woodruff-Pak, 1997). This view of delay conditioning is similar to earlier accounts of classical conditioning that emphasized the importance of associative strength (Bush & Mosteller, 1951;Prokasy & Kumpfer, 1969).…”
Section: Discussionsupporting
confidence: 68%
“…The finding that conditioned responding was influenced not by expectancy but by the recent frequency of CS-alone and CS-US trials provides particularly strong evidence that delay eyeblink conditioning in humans is an example of nondeclarative memory and is unrelated to awareness (Clark & Squire, 1998;Grant, 1973;Papka, Ivry, & Woodruff-Pak, 1997). This view of delay conditioning is similar to earlier accounts of classical conditioning that emphasized the importance of associative strength (Bush & Mosteller, 1951;Prokasy & Kumpfer, 1969).…”
Section: Discussionsupporting
confidence: 68%
“…I have not been able to gain access to this document, and as a consequence, these data were not included. Note that Prokasy and Kumpfer (1969) also reported data that, when reorganized as in Perruchet (1985), exhibited the same upward trend. However, the data were reported in a way that makes it impossible to infer whether the linear trend was significant.…”
mentioning
confidence: 64%
“…1This terminology, however, does not do justice to earlier seminal studies by William Prokasy (Prokasy & Kumpfer, 1969; Williams & Prokasy, 1977). …”
mentioning
confidence: 99%
“…In other words, the nient ratio facilitated awareness of the CS-UCS fine-grain sequential trends were exactiy opposite contingency. That is, since it has been reported that to those obtained with skeletal response systems differential performance does not occur until that (Holmes & Gormezano, 1970;Prokasy & Kumpfer, 1969;Thomas & Wagner, 1964).…”
Section: Strength Leamingmentioning
confidence: 96%